Nutrition, malnutrition and dietary interventions in inflammatory bowel disease - Sinagra, Emanule; Tomasello, Giovanni; Raimondo, Dario; Rossi, Francesca; Facella, Tiziana; Cappello, Francesco; Damiani, Provvidenza; Abruzzo, Alida; Bruno, Antonio; Palumbo, Vincenzo Davide; Cosentino, Loretta; Cottone, Mario; et al. (Progress in Nutrition, 2014)
Inflammatory Bowel Disease (IBD), which includes both Crohn’s Disease (CD) and Ulcerative Colitis (UC), is a chronic idiopathic inflammatory disorder affecting the gastrointestinal tract. Diet, as a source of luminal antigens, is thought to be an important factor in the pathogenesis of IBD. Often the nutritional status of patients is significantly compromised, particularly in CD. Several factors, including drug-nutrient interactions, disease location, symptoms, and dietary restrictions can lead to protein energy malnutrition and specific nutritional deficiencies. Solid evidence regarding the accountability of certain dietary components in the etiology of IBD are lacking. With regard to malnutrition, its consequence are growth failure, weight loss, bone disease, and/or micronutrient deficiencies, although micronutrient deficiency in IBD in most cases does not tend to have any evident clinical manifestation, except with regard to iron, folic acid, and vitamin B. Nutritional supplementation is essential for patients with evidence of malnutrition to increase calorie and protein intake. Nutritional supplementation can also have efficacy in the induction and maintenance of remission in adults with CD, however it does not replace other treatments. Aim of this review is to discuss the role of nutrition and nutrients’ deficiencies in the clinical setting of IBD, and to analyze efficacy and safety of the dietary interventions in patients with IBD.